An Indonesian Standard of Lithium-ion Battery Cell Ferro Phospate for Electric Vehicle Applications - Wahyudi Sutopo; Evizal Abdul Kadir (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In general, the process of developing new standards had problems in early the development process. In particular to identify what steps are necessary to develop new standards. Methodology of writing this article was conducted using the methodology of FACTS (Framework for Analysis, Comparison and Testing of the Standard). The results of this paper are the new standard for the Indonesian National Standard of Lithium-ion Battery Cell Ferro Phosphate for Electric Vehicle Applications.The standard of development data is can be use by automotive industrial and also for the government to decide new policy on electric vehicle especially in Indonesia.